Tectonic significance of the cumulate gabbros within Kuluncak Ophiolitic suite (Malatya, SE Turkey) inferred from geochemical data - Camuzcuoğlu, Murat; Bağcı, Utku; Koepke, Jürgen; Wolff, Paul Eric (Ofioliti, 2017)
The Kuluncak (Malatya) ophiolite in the Eastern Tauride, Turkey, consists of mantle tectonites, ultramafic-mafic cumulates, isotropic gabbros, a sheeted dike complex, plagiogranites, and a volcanic complex. The best exposure of the mafic cumulate rocks of the Kuluncak ophiolite is in the Hekimhan region, where they are represented by olivine gabbro and gabbro showing orthocumulate to mesocumulate textures. The cumulus and postcumulus minerals do not show significant zoning. The crystallization order of the cumulates is olivine, plagioclase, clinopyroxene and orthopyroxene. Whole-rock major- and trace-element geochemistry of the mafic cumulate rocks indicates that the primary magma generating the Kuluncak ophiolite is similar in composition to those observed in modern island-arc tectonic settings. Rare earth element (REE) concentrations of the mafic cumulates exhibit depleted light rare earth element (LREE) patterns, with CeN/SmN and CeN/YbN ratios ranging from 0.21 to 0.75 and from 0.17 to 0.66, respectively. The coexistence of anorthite-rich plagioclase (An73.4-93.7), highly magnesian olivine (Fo65.2-86.9), clinopyroxene (Mg#75-92.1), and orthopyroxene (Mg# 77.6-84.3) in the cumulate gabbroic rocks is indicative of an intraoceanic subduction setting and suggests that the Kuluncak ophiolite was formed during the Late Cretaceous closure of the Inner Tauride Ocean.